2005
DOI: 10.1111/j.1346-8138.2005.tb00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical Antibiotic Treatment of Impetigo with Tetracycline

Abstract: Forty-nine children aged 0.2-13 years with bullous and eroded lesions, from which Staphylococcus aureus was isolated, were diagnosed with impetigo and entered into a randomized, open-labeled trial of topical oxytetracycline hydrochloride (tetracycline) compared with a combination of topical tetracycline and oral antibiotics. After one week of topical tetracycline treatment, 22 of the 28 patients were clinically cured, and the remaining six patients had improved. In the other treatment group, 14 patients of 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The diagnosis is mainly based on clinical examination of symptoms such as honey-coloured crusting and history of the patient. Treatment is mainly antibiotics (local and systemic) and wound care 3 4Learning points

Diagnosis is clinical.

…”
Section: Descriptionmentioning
confidence: 99%
“…The diagnosis is mainly based on clinical examination of symptoms such as honey-coloured crusting and history of the patient. Treatment is mainly antibiotics (local and systemic) and wound care 3 4Learning points

Diagnosis is clinical.

…”
Section: Descriptionmentioning
confidence: 99%
“…In many rural pharmacies, tetracycline ointment is still available and is widely used for the treatment of superficial skin lesions, even though some bacterial infections will be unresponsive. There is one recent study using topical tetracycline ointment from Japan that showed that it was as effective as a combination of the same ointment and erythromycin; there was no mention of drug resistance in this community (60). Topical neomycin, as well as bacitracin, is also widely available, but associated with identifiable levels of treatment failure, as well as carrying a risk of sensitization or adverse effects.…”
Section: Pyodermasmentioning
confidence: 99%
“…Tetracycline is a broad‐spectrum polyketide antibiotic produced by the Streptomyces bacterium, working by the inhibition of the prokaryotic 30S ribosome, by binding aminoacyl‐tRNA. Tetracycline is primarily used for the treatment of acne vulgaris and rosacea but is frequently used for minor skin infection such as localized impetigo (33). Because the drug is a photosensitizer, its use is not advised when exposure to the sun or intense light is expected.…”
Section: Antibiotics Available For Topic Use In Dermatologymentioning
confidence: 99%